Accounting Students' Work Readiness; Will It Be Influenced By Work Motivation And Practical Field Work Experience? - Endrawati, Endrawati; Herman, Lisa Amelia; Alfian, Nurul Afifah (Jurnal Ilmiah Poli Bisnis, 2024)
This study's goal is to ascertain how accounting students at Politeknik Negeri Padang's level of workplace motivation and practical field experience affect their ability to enter the workforce. Work preparedness is the dependent variable, whereas work motivation and practical field experience are the independent factors employed in this study. The population of this study consists of Politeknik Negeri Padang accounting majors who are currently enrolled and have finished their Practical Field Work (PFW). With 102 respondents in the sample, the sampling was done using purposeful sampling, and the data were collected using primary sources. Data is acquired by distributing surveys to accounting students at Politeknik Negeri Padang using a google form and collecting their responses. Software called SPSS V.25 is used to process the data. The study's findings show that the association between work preparedness and the work motivation variable is both favorable and significant. Work preparedness and the PFW Experience variable have a favorable and substantial association.